THE PERFORMANCE OF BANKS IN INDONESIA: THE EFFECT OF AUDIT COMMITTEE, BOARD OF COMMISSIONERS, AND PROPORTION OF INDEPENDENT COMMISSIONERS - Salasatie, Eka Yeni; Haryanto, Eko; Fakhruddin, Iwan; Pratama, Bima Cinintya (Juremi: Jurnal Riset Ekonomi, 2023)
This research was conducted to examine the factors that influence company performance, especially those related to the role of corporate governance. With good corporate governance, company performance can grow. This study aims to determine the effectiveness of implementing good corporate governance through the existence of an audit committee, a board of commissioners, and an independent board of commissioners in improving performance. ROA is used to measure company performance. This study focuses on conventional banks registered with OJK in Indonesia from 2019-2021. Purposive sampling was used for the sampling technique, and 41 samples were obtained. Multiple linear regression was the analytical method used to test the hypothesis.